2017
DOI: 10.1159/000477331
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Collection by Vaginal Lavage for the Detection of HPV and High-Grade Intraepithelial Neoplasia

Abstract: Objective: To compare the results of cervical cytology and high-risk HPV tests using samples obtained using two different collection modalities in a population of Brazilian women: self-collection (vaginal lavage) and cervical Pap testing. Methods: We enrolled 204 women who were aged 18-64 years and had previously obtained abnormal cervical cytology test results; 83.8% of them agreed to participate. The sample was divided into two aliquots: one for the cytological study and one for the molecular analysis of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Sampling accuracy could potentially be increased by refining self-swabbing instructions. Additionally, several self-collection devices and methods have been used and are currently under evaluation, such as cytobrush,[ 31 , 32 , 58 ] tampon,[ 59 , 60 ] cervical lavage,[ 61 , 62 ] and dry storage and transport devices;[ 63 , 64 ] it is possible that they may be less prone to user error, perform better than the self-swab, and warrant future evaluation in TM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling accuracy could potentially be increased by refining self-swabbing instructions. Additionally, several self-collection devices and methods have been used and are currently under evaluation, such as cytobrush,[ 31 , 32 , 58 ] tampon,[ 59 , 60 ] cervical lavage,[ 61 , 62 ] and dry storage and transport devices;[ 63 , 64 ] it is possible that they may be less prone to user error, perform better than the self-swab, and warrant future evaluation in TM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The home self-sampling option could be particularly favorable as an alternative to clinic visits in face of the current COVID19-pandemic, plus being convenient and cost-effective (9). Self-collection of samples for HPV testing is becoming an increasingly accepted, and even preferred cervical screening option for many women (34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of this method is the leakage of fluid out of vagina, which results in partial loss in sample and discomfort of women. Besides, a study in Brazil found that self-collected lavage sensitivity for CIN 2+ cytology and HPV DNA results are only 33.3 % and 50 %, which is much lower than cytology samples obtained by clinicians (Kuil et al, 2017). A similar results for CIN 2+ sensitivity was reported at 42 %, but with higher sensitivity for HPV DNA tests at 81 % (Nobbenhuis et al, 2002) To solve the issues mentioned, Rovers® Medical Devices came up with a vaginal lavage device known as Delphi screener as shown in Figure 2.…”
Section: Self-sampling Devicesmentioning
confidence: 90%